Gastronomy as a means for the development of social innovations - Mejía-Rivas, Mariana; Maldonado-Pérez, Luz Guiomar (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This work presents the results of the research on characteristics of social innovation based on gastronomy. The research had a qualitative focus and a comprehensive design. The characteristics of the social innovations given from gastronomy were taken as the unit of analysis and as the unit of understanding the concept, method and validation of social innovation carried out from gastronomy. A choice was made from a textual corpus of 21 articles. which should refer to Colombian cases and work on social innovation processes that included gastronomy. The tool for the analysis of information was Atlas T. The results express that processes of social innovation can be promoted from gastronomy and that the characteristics attributed to social innovation can also be attributed to social innovation from gastronomy. It is concluded that gastronomy can be a tool or means for the development of social innovations that can generate changes in the eating habits of a community; as well as a tool for a current and relevant problem such as food security.